PENENTUAN BEBAN KERJA DAN JUMLAH TENAGA KERJA OPTIMAL PADA PRODUKSI TAHU - Kiki Roidelindho (Universitas Putera Batam, 2017)
This study aims to understand the standard time, workload and the amount of labor required in a single cycle of manufacturing work to know the production capacity. Work time measurement using Stopwatch Time Study and Work Sampling, adjustment factor using westinghouse method. Elements of work in this study consists of grinding process, boiling process, filtering process, the addition of vinegar, the process of formation and cutting process. From the working elements, the value of cycle time in the process of making tofu in the overall work element is 83.51 minutes, normal time of 95.19 minutes and standard time of 105.66 minutes, with a daily standard output of 3,634 pcs / day. Working load on production process is 0.26 minutes and workforce is 3 workers.